The effects of α and β blockade on ventilatory responses to exercise in chronic heart failure. Issue 10 (15th September 2003) - Witte, K K A; Thackray, S D R; Nikitin, N P; Cleland, J G F; Clark, A L
Abstract : Objective: To assess the influence of acute α and β blockade on ventilation and symptoms of breathlessness during exercise in patients with chronic heart failure and in controls. Methods: 11 patients with chronic heart failure and 11 control subjects underwent repeated exercise testing with metabolic gas exchange after random, double blind administration of either an α blocker and placebo, a β blocker and a placebo, both an α blocker and a β blocker, or double placebo. Results: Patients had a lower peak oxygen consumption (mean (SD) 20.7 (4.9) v 37.6 (9.6) ml/kg/min, p < 0.0001) and a steeper slope relating ventilation to carbon dioxide production (VE/V̇co 2 slope) (26.5 (4.1) v 37.1 (8.2), p = 0.0011), than controls. Blood pressure was lower following α and β blockade (p < 0.05) and the gradients of the slopes relating heart rate to oxygen consumption following the β blocker were reduced (p < 0.05). Exercise time and peak ventilatory variables following β or α blockers were unchanged. Ventilation was reduced during submaximal exercise following the active medications. Combined α and β blockade produced the greatest difference (p < 0.005), but the α and β blockers alone also reduced ventilation (p < 0.05). There was no difference in perceived exertion during exercise with any of the treatments. Conclusion: Acute sympathetic inhibition can reduce submaximal ventilation during exercise in patients with heart failure and control subjects, suggesting that autonomic nervous system activation has an important role in the abnormal ventilatory response to exercise in chronic heart failure.